2012
DOI: 10.2174/1876402911204030186
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optimisation of IrO2 Electrocatalysts by Adams Fusion Method for Solid Polymer Electrolyte Electrolysers

Abstract: Felix, C., et al. (2012). Synthesis and optimisation of IrO2 electrocatalysts by Adams fusion method for solid polymer electrolyte electrolysers. MICRO AND NANOSYSTEMS, University Abstract: IrO2 as an anodic electrocatalyst for the oxygen evolution reaction (OER) in solid polymer electrolyte (SPE) electrolysers was synthesised by adapting the Adams fusion method. Optimisation of the IrO2 electrocatalyst was achieved by varying the synthesis duration (0.5 -4 hours) and temperature (250 -500°C). The physical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 23 publications
(28 reference statements)
7
50
0
Order By: Relevance
“…[43][44][45][46]48,[62][63][64] In the majority of those studies, both activity and stability were estimated by studying currentpotential profiles. For instance, based on an accelerated corrosion test by detecting electrode end-of-life, Kötz and Stucki showed that in comparison to pure RuO 2 the corrosion rate of the mixed Ir-Ru oxide anodes is at least an order of magnitude lower.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46]48,[62][63][64] In the majority of those studies, both activity and stability were estimated by studying currentpotential profiles. For instance, based on an accelerated corrosion test by detecting electrode end-of-life, Kötz and Stucki showed that in comparison to pure RuO 2 the corrosion rate of the mixed Ir-Ru oxide anodes is at least an order of magnitude lower.…”
Section: Discussionmentioning
confidence: 99%
“…Since no inexpensive and suitable replacement for Ir has been found so far, current research efforts are directed toward a more efficient utilization of Ir based catalysts. 4 Nanoparticulated materials efficiently dispersed on a support, [5][6][7][8] highly porous layers, [9][10][11] core shell 12,13 and mixed oxide systems [14][15][16] have been suggested to reduce the loading of expensive elements. An alternative way is the structural modification of iridium oxides, e.g.…”
mentioning
confidence: 99%
“…Therefore, 5 h tests cannot guarantee that the investigated material is indeed stable. Other authors used chronoamperometry for 0.5 h 34 or chronopotentiometry for 15 h, 6 25 h 36 and 120 h. 5 Instead, investigation of the actual loss of active material directly during polarization can be very helpful to assess the stability on a long run. 37 Such data can be used for estimation of the electrodes end-of-life.…”
mentioning
confidence: 99%
“…IrO 2 was synthesised using an adaptation of Adams’ fusion method that is widely applied to the synthesis of noble metal oxide nanoparticles [51,54,55]. The original method involves fusion of a metal chloride precursor with NaNO 3 in air at an elevated temperature, resulting in the formation of the metal oxide and NaCl.…”
Section: Methodsmentioning
confidence: 99%